Association between nutritional status and serum leptin among newly diagnosed breast cancer patients in Hospital Universiti Sains Malaysia (Hospital USM) : a case control study - Ismail, Ahmad Karami (2016)
Breast cancer incidences are increasing worldwide. In Malaysia, the most commonly diagnosed cancer among Malaysian women is breast cancer about 29.9% of new cancer cases and The National Cancer Registry (2006) reported that there were 3,525 female breast cancer cases in Malaysia. Various studies reported that excessive body weight might increase the risk of breast cancer and obese people have higher serum leptin level. This study was carried out to investigate the relationship between nutritional status and serum leptin among newly diagnosed breast cancer patients in Hospital USM. This case control study involved 46 newly diagnosed breast cancer patients who were not undergone any treatment a n d 4 6 c o n t r o l s aged between 20-70 years. Informed consent was obtained from each study subject. Nutritional parameters used were macronutrient intake as assessed by 1-day dietary records(1DDR), anthropometry (weight, height, waist & hip circumference, body mass index, BMI) and body composition data (bio-electrical impedance ,BIA). Serum Leptin were measured by immunoassay using Human Leptin ELISA Kit (AssayMax Human Leptin, Cat.No:EL2001-1; AssayPro, USA). Overall, early menarche were at high risk of getting breast cancer by 3 folds [Crude OR 2.9 (95% CI=0.2-1.0)] (p < 0.05) as compared to those who were menarche after 12 years old. Being menopause might increase breastcancer risk by 3 folds [Crude OR 3.0 (95% CI=1.2-7.0)] (p < 0.05) when compared with pre-menopause study subjects. The BMI of breast cancer patients (24.5 ± 3.8 kg/m2) and controls (23.2 ± 4.8kg/m2) were not differed statistically (p>0.05). Percentage of body fat (measured by BIA) for cases (36.2 ± 8.7 %) were significantly higher compared with controls (31.2 ± 8.5%) (p<0.05) and subjects with BIA more than 32% were at higher risk of getting breast cancer by 6 folds [Crude OR =5.9 (95% CI=2.4-14.4)] (p < 0.05) compared with subjects BIA less 32%. Furthermore, 72% of breast cancer cases had abdominal obesity (WHR more than 0.85) compared to controls (22%) and the study result had shown study subjects with abdominal obesity have eight time higher risk of getting breast cancer as compared to those with waist to hip ratio less 0.85 [Crude OR= 8.0 (95% CI=3.2-20.4)](p < 0.05). Energy intake of cases (1397.0±311.0 kcal/d) were significantly lower than controls (1693.7±379.5 kcal/d) (p<0.05).The proportion of energy derived from protein in breast cancer cases was higher as the recommended nutrient intake for Malaysians (RNI) 2005. Serum leptin level was significantly higher in breast cancer cases (18.1 ± 4.63 ng/ml) as compared to controls (14.7 ± 4.43 ng/ml) (p<0.05). Positive relationship had been found between serum leptin level and BIA, waist and WHR, supporting the evidence that obesity was related to high leptin levels in breast cancer. In conclusion, early menarche (before 12 years old), menopause and obesity especially abdominal obesity increased breast cancer risk. Serum leptin could be an indicator for breast cancer risk.